The Effectiveness of the Triangle Run Exercise Method in Improving Aerobic Resistance Soccer Player - Riyan Hardinata; Uray Gustian; Rahmat Putra Perdana (JUARA : Jurnal Olahraga, 2021)
The characteristics of soccer which have a wide field and also a long duration of play require soccer players to have high aerobic endurance. Good aerobic endurance should be owned by every player in order to support a performance at the time of the field. There are so many exercises that can be used to increase endurance, but there is no reference for effective and efficient training methods for developing aerobic endurance. This study aims to test appropriate and effective training methods to increase endurance. The experimental design was carried out by providing a triangle run training method through walking, jogging and sprinting activities. The research was tried out on the Mensere BMC club, amounting to fifteen people. The results showed an increase in the aerobic endurance of soccer players. The increase occurred because the triangle run training method provided had similar activities in soccer, namely walking, jogging and sprinting, which made players happy and the training process, training program and appropriate training methods were possible, so that there could be improvements. The conclusion is that the triangle run training method can increase the endurance of soccer players.